Development of supercritical fluid extraction for the recovery of betacyanins from red pitaya fruit (Hylocereus polyrhizus) peel: a source of natural red pigment with potential antioxidant properties - Fathordoobady, Farahnaz; Abd Manap, Mohd Yazid; Selamat, Jinap; Pratap Singh, Anubhav (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
In the present work, supercritical fluid extraction (SFE) with CO2 as solvent and EtOH/water (v/v) as co-solvent was optimised by applying 23 factorial experimental design for the extraction of betacyanins from red pitaya fruit (Hylocereus polyrhizus) peel. Three independent variables of pressure (20-30 MPa), temperature (40-60°C) and co-solvent concentration (10-20%) were chosen for response variables. With the 2 mL/min flow rate of CO2, the dynamic time of extraction was found to be 90 min. The linear effects of main factors and interactions were evaluated. The calculated response surface model for the pressure/temperature was found to be significant for all the dependent variables. At optimal condition of SFE, the response variables were assessed as maximum extraction yield of 4.09 ± 0.69%, total betacyanins content of 25.49 ± 1.54 mg/100 mL, redness (a*) of 58.18 ± 0.82, and IC50 (antioxidant activity) of 1.34 ± 0.12 mg/mL for the experimental peel extracts. The optimal levels of independent variables were validated for the experimental responses as predicted by the mathematical model. The reliability of this method was confirmed as there was no significant difference between experimental and predicted values. The HPLC-MS profile of betacyanins extract comprised of both acylated and non-acylated betacyanins constituents.